Antibiotic resistance spectrums of Escherichia coli and Enterococcus spp. strains against commonly used antimicrobials from commercial meat-rabbit farms in Chengdu City, Southwest China - Sun, Chen; Wang, Ziye; Li, Yan; Huang, Jian (Frontiers in Veterinary Science, 2024)
The antimicrobial resistance (AMR) is commonly associated with inappropriate use of antibiotics during meat-rabbit production, which poses unpredictable risk to rabbit welfare and public health.However, the epidemiological dynamic of antibiotic resistance among bacteria indicators derived from local healthy meat-rabbits is less studied. To bridge the knowledge gap between antibiotic use and AMR distribution , a total of 75 Escherichia coli (E. coli) and 210 Enterococcus spp. strains from fecal samples of healthy meat-rabbits were successfully recovered.The antibiotic susceptibility tested by Kirby-Bauer (K-B) method revealed that diverse AMR phenotypes against 7 commonly used antimicrobials including ampicillin (AMP), amoxicillinclavulanic acid (A/C), doxycycline (DOX), enrofloxacin (ENR), florfenicol (FFC), gentamicin (GEN) and polymycin (PBM) were observed among majority of E. coli and Enterococcus spp. strains in two farms, although the distribution pattern of antibiotic resistance between young and adult rabbits was similar. Among them, 66 resistant E. coli strains showed resistance against 6 antimicrobials except for PMB. However, the 164 resistant Enterococcus spp. strains only exhibited acquired resistance against DOX and GEN. Notably, the DOX-based AMR phenotypes for E. coli and Enterococcus spp. strains were predominant, indicating the existing environmental stress conferred by DOX exposure. The MICs tested by microbroth dilution method were consistent with the AMR phenotypes and suggested elevated level of antibiotic resistance for resistant bacteria.Unexpectedly, all GEN-resistant Enterococcus spp. strains demonstrated high level gentamicin resistance (HLGR). By comparison, the blaTEM, tetA, qnrS and floR were highly detected among 35 multi-resistant E. coli strains, and aac[6']-Ie-aph[2']-Ia genes widely spread among the 40 doubleresistant Enterococcus spp. strains, which may conferred the resistance to specific antimicrobials.Nevertheless, the presence of ARGs were not concordant with the resistant phenotypes for a portion of resistant bacteria.In conclusion, the distribution of AMR and ARGs are prevalent in healthy meat-rabbits, and the therapeutic antimicrobials use in farming practice may promote the antibiotic resistance transmission among indicator bacteria. Therefore, periodic surveillance of antibiotic resistance in geographic locations and supervisory measures for rational antibiotic use are imperative strategies for combating the rising threats posed by antibiotic resistance, as well as maintaining rabbit welfare and public health.